Dysfunction of Inflammatory Pathways and Their Relationship With Psychological Factors in Adult Female Patients With Eating Disorders - Javier R. Caso; Javier R. Caso; Karina S. MacDowell; Karina S. MacDowell; Marta Soto; Marta Soto; Francisco Ruiz-Guerrero; Álvaro Carrasco-Díaz; Juan C. Leza; Juan C. Leza; José L. Carrasco; José L. Carrasco; et al. (Frontiers Media S.A., 2022)
The attempts to clarify the origin of eating disorders (ED) have not been completely successful and their etiopathogenesis remains unknown. Current research shows an activation of the immune response in neuropsychiatric diseases, including ED. We aimed to investigate immune response parameters in patients with ED and to identify psychological factors influencing the inflammatory response. The relationship between inflammation markers and impulsivity and affective symptomatology was explored as well. Thirty-four adult female patients with current diagnosis of ED, none of them under psychopharmacological treatment (excluding benzodiazepines), were included in this study. Patients were compared with a healthy control group of fifteen adult females. The levels of inflammatory markers and indicators of oxidative/nitrosative stress were evaluated in plasma and/or in peripheral blood mononuclear cells (PBMCs). Subjects were assessed by means of different ED evaluation tools. Additionally, the Barratt Impulsiveness Scale, the Montgomery-Asberg Depression Rating Scale and the Hamilton Anxiety Rating Scale were also employed. Patients with ED shown increased plasma levels of the pro-inflammatory nuclear factor kappa B (NFκB) and the cytokine tumor necrosis factor-alpha (TNF-α), among other factors and an increment in the oxidative/nitrosative stress as well as increased glucocorticoid receptor (GR) expression levels in their PBMCs. Moreover, the inflammatory prostaglandin E2 (PGE2) correlated with impulsiveness and the anti-inflammatory prostaglandin J2 (15d-PGJ2) correlated with depressive symptomatology. Our results point towards a relationship between the immune response and impulsiveness and between the immune response and depressive symptomatology in female adult patients with ED.